Smoking among pregnant women attending philanthropic maternity in São Paulo (Br - Machado Costa Lopes, Natália; Tsunechiro, Maria Alice; Almeida Pina-Oliveira, Alfredo; Chiesa, Anna Maria (O Mundo da Saúde, 2015)
The study aimed to verify the behavior of smoking during pregnancy in relation to: the prevalence of smoking, the char- acterization of the smoking history of the mother, the levels of nicotine dependence and the relationship between the number of cigarettes smoked and the birth weight of newborns. There were interviewed 273 mothers between November 2012 and January 2013, at a philanthropic maternity hospital in Sao Paulo. The results revealed a prevalence of 11% of pregnant smokers; most of them had mild nicotine dependence. The average age of onset of cigarette consumption was 15,6 years. The birth weight from newborns of smoking mothers was statistically lower in comparison to the birth weight from newborns of non-smoking women. The approach of prenatal smoking is insufficient, in which the majority of women are asked about the consumption of cigarettes, but the guidance is performed mostly for women who smoke. Thus, women’s knowledge about smoking and newborn health is low, respiratory problems are the most remembered by them; however, 35.9% of women were unable to name any pathology associated with cigarette and the newborn. About the harms to ma- ternal health, cancer was the most remembered. It was observed that it is necessary to intensify the approach of smoking at prenatal period, warning pregnant women about the risks and harms caused by cigarette for both the mother and the newborn, as there are still a lot of women who do not know basic information about the subject.